SD Al Hikmah Surabaya's Branding Strategy to Maintain the Image of an Upper Segment Islamic School - Rahmawati, Farah Nabila; Aji, Gilang Gusti (The Commercium, 2025)
This research is entitled “Branding Strategy of SD Al Hikmah Surabaya to Maintain the Image of Upper Segment Islamic School”. This study aims to analyze the branding strategy applied by SD Al Hikmah in maintaining the image of the upper segment Islamic school. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation analysis. The results showed that SD Al Hikmah Surabaya implemented a branding strategy through four main stages, namely brand identity, brand personality, brand positioning, and brand communication. The implementation of this strategy is reflected in various programs such as grand opening and trial class, utilization of Sekolahku learning platform, activation of social media especially Instagram, information disclosure, and building harmonious relationships between teachers, students, and parents. This research contributes to the understanding of branding strategies in the context of Islamic education, especially for schools that target the upper segment. The implications of this research can be a reference for other Islamic education institutions in designing effective branding strategies to build and maintain the school's image in the midst of increasingly fierce competition.